THE EFFECTIVENESS OF THE MNEMONIC METHOD TO IMPROVE LONG-TERM MEMORY ON TRIGONOMETRIC FUNCTION LIMITS MATERIAL - Sri Murwantini; Ratna Pancawati (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
This research aims to determine the effectiveness of applying the mnemonic method which is linked to long-term memory in the material on limits of trigonometric functions in basic calculus courses in the Palangka Raya University mechanical engineering education study program. The research is action research based on the Kurt Lewin model which consists of several stages including: planning, action, observation and reflection. The research subjects were 44 students taking basic calculus courses. The results of the research show that the mnemonic method is effective for improving long-term memory in Trigonometry function limits material in basic calculus courses in the Mechanical Engineering Education Study Program, Palangka Raya University. This can be seen in the average test result after being given lectures using the mnemonic method, which is 70.5 with classical completeness achieved being 88.6%. Thus, the expected classical completeness of 75% was achieved. Student responses to the use of mnemonic methods in lectures. As many as 95% of students agreed that lectures were fun. The majority of students are actively involved in lectures using this mnemonic method, where as many as 90.9% agree and it is easier for students to remember mathematical formulas in the material on limits of trigonometric functions with this mnemonic method, where as many as 97% agree. The majority of students agree that the mnemonic method needs to be used again in the next lecture material which contains many mathematical formulas, with 90.4% agreeing.